Asymmetric Evans syn‐Aldol Reactions of Terpene‐Derived Enals: Scope and Limitations. Issue 30 (4th September 2014) - Kriening, Sebastian; Evagelou, Athanasios; Claasen, Birgit; Baro, Angelika; Laschat, Sabine
Abstract: The ( E )‐ and ( Z )‐terpene‐based aldehydes6b and6c with a silyl ether function in the γ‐position were prepared and investigated in boron‐mediated asymmetric Evans aldol reactions. Screening experiments of chiral N ‐acylated oxazolidinones7, which are conveniently accessible from 5‐methyl‐5‐hexenoic acid and Evans oxazolidinone auxiliaries, with various boron triflates and terpenoid neral ( Z )‐6a as aldehyde component, provided conditions in which highly selective formation of syn ‐aldol adduct5a occurred and competing C=C double bond isomerization to10 was completely suppressed. Applying the optimized conditions to O ‐silylated aldehydes6b and6c and N ‐acyloxazolidinone derivative ( R )‐7a confirmed the syn ‐selectivity and gave the appropriate products syn ‐5b, c and syn ‐21b, c in good yields. In the case of neral‐derived syn adduct5a, the configuration of the new stereogenic centers C‐2/C‐3 could be assigned as (2 R, 3 S ). Abstract : The asymmetric Evans aldol reaction could be successfully applied to terpene‐based ( E )‐ and ( Z )‐aldehydes and N ‐acyloxazolidinones, giving syn ‐aldol adducts with high selectivity. Isomerization at the double bond was not observed.